2015
DOI: 10.1111/dth.12228
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of plasma rich in growth factors (PRGF) in skin photodamage: Clinical response and histological assessment

Abstract: Skin ageing is characterized by small and fine wrinkles, roughness, laxity, and pigmentation as a result of epidermal thinning, collagen degradation, dermal atrophy, and fewer fibroblasts. Plasma rich in growth factors (PRGF) is an autologous plasma preparation enriched in proteins obtained from patient's own blood aimed at accelerating tissue repair and regeneration. To evaluate the benefits of PRGF in skin photodamage, 10 healthy volunteers were treated with three consecutive intradermal injections of PRGF i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 8 publications
(8 reference statements)
4
25
0
3
Order By: Relevance
“…As it is showed in the pre‐ and post‐treatment images and patient/clinical surveys, a soft tissue augmentation effect was noticed along with an overall skin quality improvement in terms of hydration, elasticity, wrinkle reduction and general satisfaction scores. These results are consistent with other reports in which autologous growth factors were intradermally applied with the aim of boosting the dermo‐epidermal renewal of aged patients . Thus, the AG not only acts as a temporary biodegradable volumizer but also and more importantly, as a soft tissue stimulator.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As it is showed in the pre‐ and post‐treatment images and patient/clinical surveys, a soft tissue augmentation effect was noticed along with an overall skin quality improvement in terms of hydration, elasticity, wrinkle reduction and general satisfaction scores. These results are consistent with other reports in which autologous growth factors were intradermally applied with the aim of boosting the dermo‐epidermal renewal of aged patients . Thus, the AG not only acts as a temporary biodegradable volumizer but also and more importantly, as a soft tissue stimulator.…”
Section: Discussionsupporting
confidence: 92%
“…The potential ability of PRP for activating cell tissue turnover may enhance dermal thickness, improving the tone and elasticity of skin thereby counterbalancing chronological aging mechanisms which slow metabolic activity and render skin atrophy . In fact, PRGF has proved to reverse the ultraviolet light‐derived skin photoaging, also known as solar elastosis, by inducing dermal fibroblast proliferation, preventing cellular apoptosis and promoting the neo‐angiogenesis, which is translated into a thickened dermis with newly synthetized collagen and elastic fibers …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRGF provides an optimal intracellular ionic balance with ideal pH values of 7.9 and physiological osmolarity of 300 mOsm/kg, which could be related to our results in terms of histomorphometric perifollicular tissue integrity . Previous studies have also reported the extracellular matrix remodeling effect of PRGF including collagen regeneration and elastic fiber tridimensional arrangement . This could be translated into higher percentage of viable grafts due to the lower rate of old dense and highly packaged collagen bundle accumulation over transplanted hairs resulting in a reduction of perifollicular fibrosis .…”
Section: Discussionsupporting
confidence: 76%